Prognostic significance of motor evoked potentials in surgical interventions to eliminate spinal stenosis at the cervical level - D. V. Yakovleva; D. S. Kanshina; M. G. Podgurskaya; A. N. Kuznetsov; O. I. Vinogradov; B. A. Teplykh; S. M. Magommedov (Нервно-мышечные болезни)
Introduction. Transcranial electrical stimulation is a neurophysiological method that is used intraoperatively for evaluating the conduct of a nerve impulse through the cortical-spinal tract. However, the results obtained during registration of this modality do not always correlate with the neurological status of the patient after surgery. The purpose of the study is to determine the prognostic significance of motor evoked potentials in surgical interventions for the elimination of spinal stenosis at the cervical level. Materials and methods. The study analyzed the results of 20 microsurgical root decompressions at the cervical level by eliminating spinal stenosis. Surgical interventions were performed in the neurosurgical Department of National medical and surgical center named after N.I. Pirogov from august 2018 to march 2019. Intraoperatively there were used the following modalities: motor evoked potentials, 3-channel registration of somatosensory evoked potentials from the median nerves, 8-channel electroencephalography, and train-of-four monitoring. The patients were divided into 2 groups: in the 1st group was used inhalant anesthetics, in the 2nd the anesthesia was conducted according to the protocol “Total intravenous anesthesia”. Results. Within each group, in a number of cases, there was a decrease in the response amplitude (by 80 % or more), as well as a loss of motor evoked potentials. In the “Total intravenous anesthesia” group, the current stimulation forces used to obtain motor evoked potentials did not exceed 150 mA, while in the group of inhaled anesthetics, the maximum value was 300 mA, and the average value was 170 mA. In the “Total intravenous anesthesia” group, in 2 cases, a loss of response from one myotome at the decompression phase was registered without recovery during intraoperation monitoring, in 2 cases there was the amplitude loss by 80 % or more with subsequent recovery. In the “Total intravenous anesthesia” group, the results were comparable. Conclusion. During neurophysiological monitoring in surgeries at the cervical level, the loss of motor evoked potentials from one myotome, as well as a decrease the response amplitude by 80 % or more are doubtful as a criteria for predicting neurological deficit.